"A Super Wild Story": Shared Human–Pigeon Lives and the Questions They Beg. (November 2017) - Rautio, Pauliina
The three coincidentally shared human–pigeon lives discussed in this article challenge the established conceptualization that when species meet habituation occurs, a smoothing over of differences over time because it does not account for the dynamic, affectionate, and productive nature of shared human–pigeon lives. The concept refrain works better. Concepts like habituation and refrain can be thought of as answers to questions posed by the world . Concepts are answers insomuch as they are certain ways of thinking about and acting within the world—always excluding other ways. In living and working with answers, as we do, it is easy to forget the original questions: What did the world ask of us again, and could there be other possible answers? In this article, the kind of answer that refrain is is mapped through three cases of human–pigeon lives. Rather than mechanistic and anthropocentric, refrain is an answer that directs our attention to what is dynamic, unpredictable, productive, and nonanthropocentric. It also offers possibilities to pose new questions.